2019
DOI: 10.3390/nu11122973
|View full text |Cite
|
Sign up to set email alerts
|

Giardia intestinalis and Fructose Malabsorption: A Frequent Association

Abstract: Nowadays, scientific studies are emerging on the possible etiological role of intestinal parasites in functional digestive disorders. Our study was carried out with healthy individuals (control group; n = 82) and symptomatic patients with lactose or fructose malabsorption, including positive (malabsorbers; n = 213) and negative (absorbers; n = 56) breath test, being analyzed for the presence of intestinal parasites. A high parasitic prevalence was observed in malabsorbers (41.8%), exclusively due to single-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 55 publications
0
13
0
1
Order By: Relevance
“…2a). The helminth-only group with decreased Prevotella proportions relative to the Giardiaonly group U (25) = 41, Z = 2.0125, P = 0.0457, but similar to the control group (Fig. 2b).…”
Section: Change In Bacterial Abundancementioning
confidence: 61%
See 1 more Smart Citation
“…2a). The helminth-only group with decreased Prevotella proportions relative to the Giardiaonly group U (25) = 41, Z = 2.0125, P = 0.0457, but similar to the control group (Fig. 2b).…”
Section: Change In Bacterial Abundancementioning
confidence: 61%
“…Gastrointestinal parasites may modulate intestinal inflammation, malabsorption, and microbiome changes [22][23][24][25][26]. The microbiome is associated with digestion, nutrition and health, but alterations in biodiversity can increase disease states and induce intestinal inflammation [27].…”
mentioning
confidence: 99%
“…Only few studies have reported on combined occurrence of LIT with FM. Approximately 30% of patients with FNNGIC and carbohydrate intolerance/malabsorption may have a combination of these [4,17]. A parallel occurrence, serum DAO values <10 U/mL in more than 50% combined LIT and FM patients, indicative of additional HIT, was described [18].…”
Section: Discussionmentioning
confidence: 99%
“…These functional abdominal, symptom-based, syndromes have a symptom profile comparable to food intolerance/malabsorption including fructose malabsorption (FM), histamine intolerance (HIT), and lactose intolerance (LIT) [2]. Combined appearance of these is increasingly reported and occurs in more than 30% of patients with FNNGIC and food intolerance/malabsorption [3,4]. For the clinical diagnosis of LIT and FM proved hydrogen (H 2 ) breath tests useful.…”
Section: Introductionmentioning
confidence: 99%
“…Giardia intesztinális parazitózis esetén a betegek 89,5%-ában észleltek fruktózmalabszorpciót. Kró-nikus hasi panaszok esetén, amennyiben szénhidrát-intolerancia mellett zsíroldékony vitaminok alacsony szintjét észleljük, részletes direkt és indirekt parazitológiai vizsgálat elvégzése javasolt (14).…”
Section: Fruktózmalabszorpció éS Parazitózisunclassified